Advances in processing and post-harvest management of indigenous vegetables - Singh, Sudhir; Sharma, Swati (Indian Horticulture, 2020)
The processed indigenous vegetable industry has great potential to realize the agricultural resources. There has been a huge challenge to our industry to increase the processing of the perishables to provide sufficient growth to the global trade by adding increased value to the end products. The Ministry of Food Processing, Govt. of India, also intends to increase the processing of horticultural crops from 2% to 20%, value addition from 7% to 35% and share of global trade from 1% to 3%. Farmers particularly women in rural sector can play a crucial role to give a boost in the processing of perishable products at small sector. There is an urgent need to support farmer-managed rural production and marketing ventures in horticulture, and post-harvest processing and to provide technology training and input support to farmers to take advantage of emerging high-value agribusiness sector. Agro-processing particularly indigenous vegetable processing can generate employment for whole family of farmer so that farmer’s income can be increased. Harvesting of indigenous vegetables at proper stage of maturity, storage under cold chain management and suitable processing with assured marketing of processed products can increase the income of the farmers and it would be a step towards fulfilling the mission of our Honourable Prime Minister by doubling the farmer’s income by 2022.